Relasi Timur dan Barat dalam Permasalahan Konflik Suriah - Darmiko Suhendra (Hikmah: Journal of Islamic Studies, 2019)
Based on historical fact, between Islam and the West theologically has strong bond which is on the meeting points and similarities between Islam and the West that inherit Jewish and Christian traditions. These three religions inherited the tradition of Prophet Ibrahim. However, theological similarities between Christianity and Islam precisely become t he cause of collision between two of them. Historical problem between Islam and the West can be seen from the root of the conflict that includes: theological and political. Conflict between Islam and the West is covered by political motives. On the contrary, theology is only become justification to distinguish culturally and theologically between Islam and the West, basically this difference is more encouraged by political interest. Conflicts happen in Syiria is not because of religious factor, but it is more dominated by political and economic interest. The facts prove that most of Arab countries are the eternal alliance of the Western block, which was directed by The United States as the Solely Super Power in the world. Therefore, in the effort to build agreement and global coalition, actively promote cooperation. So that, the most important thing right now is the encounter between Islam and the West, that must be interpreted as building a dialogue of Civilization, not confrontation or mutual suspicion, building ideal relationship and also the need of harmonization between Islam and the West. Keywords: West, Islam, Conflict Berdasarkan fakta sejarah, antara Islam dan Barat secara teologis mempunyai ikatan yang kuat yakni ada titik temu dan persamaan antara Islam dan Barat yang mewarisi tradisi Yahudi dan Kristen. Ketiga agama ini mewarisi tradisi Nabi Ibrahim. Namun, persamaan teologis yang ada antar Kristen dan Islam justru menjadi penyebab benturan di antara keduanya. Problem historis antara Islam dan Barat dapat dilihat dari akar konflik yang meliputi, teologis dan politis. Konflik antara Islam dan Barat tertutupi dengan motif politik. Sebaliknya, teologis hanya dijadikan justifikasi untuk membedakan secara kultural dan teologis antara Islam dan Barat, pada dasarnya perbedaan ini lebih didorong oleh kepentingan politik. Adalah konflik yang terjadi di Suriah bukanlah karena faktor agama namun lebih didominasi oleh faktor politik dan ekonomi. Fakta membuktikan, bahwa sebagian besar negara Arab adalah aliansi abadi blok Barat, yang dinakhodai langsung oleh Amerika Serikat sebagai kekuatan Super Power tunggal dunia. Oleh karena itu dalam upaya untuk membangun kesepakatan dan koalisi global, untuk secara aktif mempromosikan kerja sama. Oleh karena itu, yang terpenting saat ini perjumpaan Islam dan Barat harus dimaknai sebagai membangun dialog peradaban, bukan konfrontasi atau saling curiga, membangun hubungan yang ideal serta perlunya harmonisasi antara peradaban Islam dan Barat. Kata Kunci: Barat, Islam, Konflik